Measuring the success of learning through technology : a step-by-step guide for measuring impact and ROI on e-learning, blended learning, and mobile learning - Elkeles, Tamar; Phillips, Patricia Pulliam; Phillips, Jack J., 1945- (ASTD Press, 2014)
The challenge with e-learning lies in proving its value and showing the results. The cost savings and the outcome of the learning program must be considered to determine the true value of these programs. In this guide the authors measure the success of e-learning programs. By following the steps prescribed in this book, designers and developers can significantly affect the success of e-learning at the application and impact levels, ultimately making the ROI easy to develop. Part I of the book outlines the steps that make up the logical approach to evaluation using the ROI Methodology. Part II describes how the methodology has been applied in real-life case studies representing a variety of industries and applications, written by experienced professionals in the field of learning and development. --